Evaluation of black gram (Vigna mungo) genepool against Callosobruchus maculatus and diversity analysis inter se - PANIGRAHI, S K; TRIPATHI, K; SINGH, R; KUMAR, R; SANGHAMITRA, P; WANKHEDE, D P; SINGH, N; DUBEY, K K D; GUPTA, KAVITA (The Indian Journal of Agricultural Sciences, 2022)
The present study was carried out at ICAR-National Bureau of Plant Genetic Resources, New Delhi during 2020–21 to evaluate the differential reaction of 69 germplasm accessions representing black gram [Vigna mungo (L.) Hepper] landraces and its crop wild relatives for resistance against Callosobruchus maculatus (Fab.) under artificial infestation et-up using ‘No-choice test’ method and analyze their genetic diversity using SSR markers. After emergence of adult beetles, the accessions were studied for the growth parameters like total oviposition, exit holes, adult emergence (AE), per cent seed weight loss (PSWL) and growth index (GI), which varied significantly. Based on the key traits, viz. AE and PSWL, the accessions were categorized into six groups, viz. immune (I), resistant (R), moderately resistant (MR), moderately susceptible (MS), susceptible (S) and highly susceptible (HS). Accessions IC259504 (Vigna vexillata) and IC424616 (Vigna mungo) were immune and resistant to bruchid infestation respectively. Moreover, the genetic diversity parameters such as allele number, PIC values and observed heterozygosity indicated considerable diversity among the accessions. The reported immune and resistant accessions could be used as donor parents in the Vigna breeding programme for transferring bruchid resistance factor(s) to agronomically superior cultivars.